Neoadjuvant chemotherapy and surgery for transdiaphragmatic liver invasion of primary lung cancer. Issue 2 (22nd April 2013) - Iwata, Takashi; Takeda, Yutaka; Iida, Shin‐ichiro; Hanada, Shoji; Inoue, Hidetoshi; Nakahira, Shin; Chung, Kyukwang; Miura, Takuya
Abstract A 75‐year‐old woman presented with intermittent dull abdominal pain, gradually exacerbating over eight months. Computed tomography demonstrated a large mass straddling both the right lower lobe of the lung and the right hepatic lobe. An 18‐fluoro‐2‐deoxy‐D‐glucose positron emission computed tomography scan (PET/CT) demonstrated high accumulation in the lesion and carinal lymph nodes. Transbronchial biopsy revealed squamous cell carcinoma; thus, primary lung cancer with transdiaphragmatic invasion into the liver was diagnosed. Chemotherapy with carboplatin (AUC = 5) on day one and weekly paclitaxel (70 mg/m2) doses were introduced for four courses. The size of the main tumor was reduced and the mediastinal lymph node accumulation disappeared in a subsequent PET/CT. Thus, en‐bloc radical resection of the lung tumor by right lower lobectomy with partial resection of invaded middle lobe and the diaphragm, subsegmentectomy of the liver, and standard mediastinal dissection were undertaken. The postoperative course was uneventful and the patient was discharged on day 30. Her nutrition status dramatically improved and she gained five kilograms of body weight in two months following the resection. The patient, however, then had a fall and suffered femur and multiple pelvic fractures and died of acute pneumonia five weeks after the femur fixation and 14 weeks after the lung surgery.